Successful off-label use of omalizumab in a child with chronic spontaneous urticaria - Gonçalves, Tânia; Alen Coutinho, Iolanda; Pita, Joana Sofia; Leiria Pinto, Paula (BIRTH AND GROWTH MEDICAL JOURNAL, 2024)
Omalizumab is approved as third-line therapy for patients older than 12 years with antihistamine-refractory chronic spontaneous urticaria. The authors present the case of an eight-year-old boy with a history of migratory maculopapular skin lesions, arthralgias, and conjunctival hyperemia. Laboratory findings were unremarkable. Skin biopsy was consistent with urticaria. Treatment with oral betamethasone and quadruple dose of bilastine was initiated, with clinical resolution of arthralgias and conjunctival hyperemia, but no improvement in skin lesions. After five months of illness, the patient developed several side effects of corticosteroids and was started on cyclosporine, with no clinical response after four weeks of treatment. At this point, he was started on off-label omalizumab 300 mg every four weeks, and corticosteroid therapy was discontinued after one month of treatment. After the third administration of omalizumab, the boy achieved complete clinical resolution. Omalizumab may be an effective and safe treatment for antihistamine-refractory chronic spontaneous urticaria in pediatric age.